2022
DOI: 10.1017/s0144686x22000150
|View full text |Cite
|
Sign up to set email alerts
|

The experience of dependence on homecare among people ageing at home

Abstract: Being dependent on homecare potentially threatens a person's integrity and autonomy, particularly when people are dependent on help to manage basic bodily functions that involve intimacy and nudity, making the person vulnerable despite being in his or her own home. As the population continues to age and live longer, more people are expected to be dependent on homecare. The aim of this study was to investigate the phenomenon of dependence on homecare among people ageing at home. Individual in-depth interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…As studies from different countries have shown, home care nursing has been constrained by demands for cost-containment leading to task-oriented services (Funk et al, 2022;Martinsen et al, 2022;Strandås et al, 2019;Suhonen et al, 2018). We suggest that home…”
Section: Discussionmentioning
confidence: 87%
“…As studies from different countries have shown, home care nursing has been constrained by demands for cost-containment leading to task-oriented services (Funk et al, 2022;Martinsen et al, 2022;Strandås et al, 2019;Suhonen et al, 2018). We suggest that home…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, the findings show that this can be further understood as an intersubjective bond between the older patients and the relatives, which unfolds itself into different nuances of dependency and interdependency. Usually, dependency and especially dependency on care are experienced on an individual level [33][34][35]. However, this study emphasizes the intertwined experiences and different nuances of dependency in the relationship of the older patients and their relatives.…”
Section: Discussionmentioning
confidence: 89%
“…However, our findings also demonstrated that in some caring relationships participants hesitated to express their wishes, which may impede the development of a genuine relationship where good care may be provided (Strandberg et al, 2003). In principle, the dependent person has the possibility to verbalize precisely how he or she would like the care to be provided; however, in reality, dependent peoples’ tendency to state demands to their carers is closely related to their personality, their current situation, and their relationship with the caregiver (Martinsen et al, 2022). From an existential viewpoint, care is provided in a tiny, shared space occupied by the caregiver and the care recipient, and in this space, the caregiver is responsible for using their power to assist and underpin the dependent person’s being.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to explore the existential dimension of being dependent on homecare in general and what makes dependency bearable in particular. This article forms part of a larger study aiming to explore the experience of dependency among people ageing at home (Martinsen et al, 2022).…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation